Problems of organization of facilitation interaction between teacher and student - Prokopenko, Iryna (Journal of Education, Health and Sport, 2018)
The article is devoted to defining the essence of the concepts "interaction", "facilitation interaction", "facilitation interaction of a teacher with students" and the problem of organizing the facilitation interaction of a teacher with students. The basic ideas of facilitation interaction are due to a set of factors of the educational environment. Facilitation interaction in its structure has socio-cultural foundations that determine the methodological, theoretical and practical possibilities of facilitation as a humanistically oriented process that implements the principles of democracy and freedom in productive activities and communication, the variability of schooling. Based on the scientific analysis of foreign works of scientists, the factors contributing to the facilitation interaction are identified: actualization of the facilitation potential of the educational environment, involvement of the facilitation potential of the environment, manifestation of facilitation in a certain sphere of life, influence of the sphere its various angles. Facilitation interaction in our study, based on the scientific work of foreign scientists, is defined as subject-subject interaction, which includes emotional contact, creating an educational environment for positive motivation, joint personal growth and self-improvement of teacher and student.